TRANSFORMATION OF NEEDS OF THE DISABLED IN THE CONTEXT OF MUSIC THERAPY - Vilkeliene, Aldona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article presents the case study, which highlights the limitation of physical, social and self-expression needs, caused by disability. It is concluded that the needs of the disabled transformed during music activity and changed their hierarchy – the social needs and self-expression have become more important than physical. The disabled has established himself as an older and more experienced person’s identity, giving the advice and assessments on musical themes; a partner’s and a friend's identity - he has not complained about his pains, and has learned to notice the other people's emotions; the physical opportunities have extended as well – the disabled started exercising and began to show more willingness to move in the wheelchair. This substantiates the studies of Stige (2004), Moreno (2006), predicating that if the person's life is based on the culture and social relations, then his personal priorities change.